Pengaruh physical evidence, harga dan produk terhadap kepuasan serta dampaknya terhadap loyalitas pelanggan hypermarket - Vanessa Jacobus (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2019)
The goal of this research was to analyze the effect of physical evidence, price and products on loyalty with customer satisfaction as a mediating variable of Hypermarket A and B in East Jakarta region. The population on this research were all the people who lived in East Jakarta and Bekasi which eased the researcher to find consumers from both Hypermarkets. Sampling method was using convenience sampling technique with the calculation of sampling using Slovin formula so it obtained at least 100 samples. The source of this research was a primary and secondary source. A primary source was collected by fill the questionnaires by respondents and literature studies as a second source. The method for analysis was the classic assumption test and partial t-test. The result of the hypothesis shows that; price and product were positively impacted on customer satisfaction and so do the satisfaction on customer loyalty.